2012
DOI: 10.1002/asia.201100710
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and Dispersion of Hexagonal Boron Nitride (h‐BN) Nanosheets Treated with Inorganic Reagents

Abstract: A mixture of bulk hexagonal boron nitride (h-BN) with hydrazine, 30% H(2)O(2), HNO(3)/H(2)SO(4), or oleum was heated in an autoclave at 100 °C to produce functionalized h-BN. The product formed stable colloid solutions in water (0.26-0.32 g L(-1)) and N,N-dimethylformamide (0.34-0.52 g L(-1)) upon mild ultrasonication. The yield of "soluble" h-BN reached about 70 wt%. The dispersions contained few-layered h-BN nanosheets with lateral dimensions in the order of several hundred nanometers. The functionalized dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
105
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 62 publications
12
105
0
Order By: Relevance
“…As seen in 191.1 eV for B 1s and 397.6-398.7 eV for N 1s for boron nitride [35,36]. The B 1s and N 1s spectra of porous BN also exhibited shake-up satellite peaks, which confirm the presence of sp 2 -hybridised BN in the hexagonal phase, as previously reported [37][38][39]. In addition to BN, XPS revealed the presence of between 10 and 13 at.% ± 1 at.% of oxygen impurities (Fig.…”
Section: Resultssupporting
confidence: 83%
“…As seen in 191.1 eV for B 1s and 397.6-398.7 eV for N 1s for boron nitride [35,36]. The B 1s and N 1s spectra of porous BN also exhibited shake-up satellite peaks, which confirm the presence of sp 2 -hybridised BN in the hexagonal phase, as previously reported [37][38][39]. In addition to BN, XPS revealed the presence of between 10 and 13 at.% ± 1 at.% of oxygen impurities (Fig.…”
Section: Resultssupporting
confidence: 83%
“…29 Considering the detection limit of XRD measurement, Raman spectroscopy was further applied to explore the phase purity of the as-obtained h-BN powder. 11,24,45 In N1s spectra, the binding energy at 398.2 eV is referred to N-B bonds, 24,46 accompanied by a rather small peak attributed to N-C bonds at 399.3 eV. 2a illustrates the Raman spectrum of the h-BN powder conducted under ambient conditions with a 785 nm laser line.…”
Section: Preparation Of Colloidal H-bn Nanosheet/noble Metal Compositmentioning
confidence: 99%
“…It was demonstrated that h-BN saves its hexagonal structure throughout the functionalization procedure. Its exfoliation into thin platelets upon contact with solvents is probably owing to the attachment of hydrophilic functionalities [12]. The chemical stability of BN heated at high temperatures increases as compared to the chemical stability of untreated powders due to decrease in the reactive surface and formation of more perfect crystal structure.…”
Section: Introductionmentioning
confidence: 99%